Availability, accessibility and activation of mental health services among university students in Africa: a protocol of a mixed-methods systematic review with meta-analysis and meta-synthesis - Hesborn Wao; Melvin A Wao; Ian Muriithi; Paul Seraii; Jackline Syonguvi (BMJ Open)
Introduction In Africa, the prevalence of mental health problems is higher among university students than in the general population. A number of systematic reviews and recent prevalence studies have focused on prevalence of mental health issues among college. This mixed-methods systematic review, including meta-analysis and meta-synthesis, will explore: what mental health services are available to university students; the extent to which students access available services and factors associated with service access; and the degree to which students activate (use) accessible services and factors associated with service activation.Methods and analysis We will conduct electronic literature search of the following databases: PubMed, Cochrane Library, Semantic Scholar, ERIC, Trip Database, Medline and PsycINFO. Disagreement, if any, will be resolved by a third reviewer. Two reviewers will independently assess the methodological quality of included studies using relevant tools. For cross-sectional studies, we will use the Joanna Briggs Institute Checklist for Analytical Cross Sectional Studies whereas qualitative or mixed-methods studies will be assessed using the Critical Appraisal Skills Programme. OR, risk ratio or mean difference with 95% CI will be considered as the effect size. We will assess heterogeneity between studies by appropriate subgroup analyses. Publication bias will be detected using funnel plots.Ethics and dissemination Ethical clearance is not required as we are not collecting primary data. Findings will be disseminated via relevant scientific conferences and peer-reviewed publications.PROSPERO registration number CRD42022296870.